Association of ABO blood group with plasmodium falciparum malaria in Sudanese population - Abdalla Mohamed; Mohammed Abdelmotalab; Mohamed Elbasheir (Journal of Research in Applied and Basic Medical Sciences)
Background & Aims: Malaria is a febrile illness with an incubation period of one week or more. Plasmodium falciparum is responsible for the most severe forms. So, this cross-sectional hospital-based study conducted to determine the association between ABO blood group and Plasmodium falciparum infection. Materials & Methods: The study was carried out in three different clinics: Rota Clinic, Military Hospital, and Bahri Hospital in Khartoum states, Sudan. The study was conducted from May to August 2017. The sample size investigated was 580 subjects, with 200 subjects found to have a positive malaria infection (80 females and 120 males). Result: The results of this study revealed an overall infection rate of 34.4%. The prevalence rates reported in Military Hospital, Bahri Hospital, and Rota Clinic were 37.1%, 34.7%, and 28.2%, respectively. The study results showed that the highest prevalence rate (60%) was among males, while rate in females was 40%. The highest prevalence rate (32%) was reported among the age group 16-30 years old, and the lowest rate (13%) was among the age group 1-15 years old. The investigation revealed that the highest prevalence rate (58%) was among the O blood group, and the lowest prevalence rate (8%) was among the AB blood group. High parasitemia was strictly confined to A and B and low parasitemia in O blood group. Conclusion: Although the results showed relation of the disease with blood group, sex, and age group, further research with more population is necessary to add more information about the role of ABO blood groups in Plasmodium falciparum malaria and to contribute to malaria prevention.